Probing of heavy metals in the feathers of shorebirds of Central Asian Flyway wintering grounds - Jeganathan Pandiyan (Nature Portfolio, 2020)
Abstract The study is intended to deliver the incidence of heavy metals in the feathers of shorebirds from two important Central Asian Flyway (CAF) migratory shorebirds wintering sites such as the Point Calimere Wildlife Sanctuary (PWLS) and Pichavaram Mangrove Forest (PMF), India. Feathers of fifteen species of shorebirds and seven different metals viz., Cu, Cr, Co, Pb, Hg, Ni and Zn were analyzed. Zn was highest in Dunlin, Little-ringed Plover, Marsh Sandpiper, and Common sandpiper, Ni showed highest in Little ringed plover, and Common sandpiper, Co, Cr, and Cu were maximum in Little stint, Marsh sandpiper, and Dunlin, respectively. The Hg was higher in Black-winged stilt, Common redshank, Curlew Sandpiper, Eurasian curlew, Lesser Sand-plover, Temminck’s stint, Kentish plover, Spotted redshank, and Wood sandpiper, the Pb found highest in Kentish plover, Painted stork, Spotted redshank, Wood sandpiper, Eurasian Curlew, and Lesser sand-plover. The concentration of metals showed significant variations among the species of shorebirds studied (P < 0.001). The mercury negatively correlated with the other metals than the other six metals studied in both the wetlands. The order of metal concentration in the feathers of shorebirds was Zn > Ni > Co > Cr > Cu > Pb > Hg. Nevertheless, the current study revealed that the level of metals in the shorebirds is alarming; since the PWLS and PMF are located along the CAF routes, it needs intensive studies on various pollutions to manage both the resident as well as migratory shorebirds.